1983
DOI: 10.1083/jcb.96.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of promyelocytic (HL-60) cells into mature granulocytes: mitochondrial-specific rhodamine 123 fluorescence.

Abstract: Rhodamine 123, a fluorescent dye which binds as a result of the transmembrane potential, was used to stain the mitochondria of HL-60 cells, a cell line established from human promelocytic leukemia cells. The DMSO-induced differentiation of promyelocytic cells into mature granulocytes caused a fourfold decrease in fluorescence intensity that paralleled the disappearance of S-phase and G2M cells. This suggests that upon myeloid differentiation whereby the cells enter an irreversible quiescent state, the mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Neutrophils also have a lowered requirement for cytochrome c for the engagement of the intrinsic pathway [28]. We confirmed that neutrophilic differentiation of HL-60 cells is accompanied by decrease in cell stainability with mitochondria-specific dyes [38]. In contrast, we did not observe the previously reported downregulation of cytochrome c [42].…”
Section: Discussioncontrasting
confidence: 33%
See 1 more Smart Citation
“…Neutrophils also have a lowered requirement for cytochrome c for the engagement of the intrinsic pathway [28]. We confirmed that neutrophilic differentiation of HL-60 cells is accompanied by decrease in cell stainability with mitochondria-specific dyes [38]. In contrast, we did not observe the previously reported downregulation of cytochrome c [42].…”
Section: Discussioncontrasting
confidence: 33%
“…In HL-60 cells, the differentiation activity of ATRA is mediated through RARα [37], while the mechanism of DMSO action is not clear [36]. However, both inducers cause the G0/G1 cell cycle arrest [13,38] and continuous cell treatment with ATRA or DMSO eventually leads to apoptosis. Both ATRA and DMSO are known to alter the expression of various apoptosis-related genes [12,14,39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of other HL-60 cell populations (Zucker et al, 1983;Collins and Foster, 1983;Ross, 1985), as well as the early volume changes noted in our studies suggested that DMSO and GM CSF might be mediating their opposing growth effects in part through changes in cell cycle kinetics. The results of flow cytometric analysis of HL-60 cells grown in 0-1.5% DMSO and 0% or 10% GCT CM are shown in Table 1.…”
Section: Effects Of Dmso and Gct CM On The Cell Cycle Kinetics Of Hl-mentioning
confidence: 76%
“…2 Accordingly, inhibitors of glycolysis such as sodium iodoacetate and 2-deoxyglucose caused a profound ATP loss with less than 1% of ATP remaining in comparison to untreated neutrophils ( Figure 1; and data not shown). Moreover, two important mitochondrial enzymes, glutamate dehydrogenase (GDH) and fumarase, which are often used as markers of mitochondria, 10-12 displayed a borderline low activity in neutrophils in contrast to HL-60 cells, which have actively respiring mitochondria 13,14 (Figure 2). At the same time, the activity of the cytoplasmic marker lactate dehydrogenase (LDH) was nearly identical in neutrophils and HL-60 cells, confirming an overall intactness of enzymes in the neutrophil cell lysates (Figure 2).…”
Section: Resultsmentioning
confidence: 99%